Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11033-009-9884-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii

Abstract: Superoxide dismutases (SODs) play important role in stress tolerance of plants. In this study, an MnSOD gene (TaMnSOD) from Tamarix androssowii, under the control of the CaMV35S promoter, was introduced into poplar (Populus davidiana x P. bolleana). The physiological parameters, including SOD activity, malondialdehyde (MDA) content, relative electrical conductivity (REC) and relative weight gain, of transgenic lines and wild type (WT) plants, were measured and compared. The results showed that SOD activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(64 citation statements)
references
References 18 publications
2
60
0
Order By: Relevance
“…Quantitative real-time PCR analysis showed that the JcCu/Zn-SOD gene was expressed in all J. curcas tissues examined and increased under NaCl stress ( Figure 3A and B). These findings generally agree with those other studies reporting increased Cu/Zn-SOD expression in plants exposed to salt stress (Hernandez et al, 1999;Wang et al, 2010). However, no significant changes in Cu/ Zn-SOD mRNA levels were observed in other experiments under NaCl treatment (MenezesBenavente et al, 2004;Jithesh et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Quantitative real-time PCR analysis showed that the JcCu/Zn-SOD gene was expressed in all J. curcas tissues examined and increased under NaCl stress ( Figure 3A and B). These findings generally agree with those other studies reporting increased Cu/Zn-SOD expression in plants exposed to salt stress (Hernandez et al, 1999;Wang et al, 2010). However, no significant changes in Cu/ Zn-SOD mRNA levels were observed in other experiments under NaCl treatment (MenezesBenavente et al, 2004;Jithesh et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Since photorespiration is considered to be important to prevent ROS accumulation (Voss et al, 2013), the postulated decreased activity of the GDH/SHMT complex could be an additional cause for oxidative stress in ftsh4. Furthermore, among the proteins carbonylated preferentially in ftsh4 is the manganese superoxide dismutase, a key enzyme for eliminating mitochondrial superoxide radicals (Wang et al, 2010). This enzyme is probably inactive in ftsh4 due to oxidative modification (Qin et al, 2009), and it was found to be highly carbonylated in all the conditions examined (Table II).…”
Section: In Ftsh4 the Defective Oxphos System Is Linked To Enhancedmentioning
confidence: 94%
“…The plant antioxidant system consists of ROS-scavenging enzymes, such as superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX), as well as low-molecular-weight antioxidants like glutathione, ascorbate, carotenoids, metallothionein, etc (Table 1). Analysis with transgenic plants overexpressing these antioxidant genes revealed that maintenance of a high antioxidant capacity in cells is linked to increased tolerance against various adverse conditions (Guo et al, 2009;Jayaraj & Punja, 2008;Tseng et al, 2007;Wang et al, 2010). Heavy metal stresses can shift the cellular balance of free radical homeostasis into terrible accumulation of H 2 O 2 .…”
Section: Heavy Metal-induced Oxidative Stress and Stress Tolerance: Cmentioning
confidence: 99%